Metal-Backed Tibial Components Do Not Reduce Risk of Early Aseptic Loosening in Unicompartmental Knee Arthroplasty: A Systematic Review and Meta-Analysis - Costa, Giuseppe Gianluca; Lo Presti, Mirco; Grassi, Alberto; Agrò, Giuseppe; Cialdella, Sergio; Mosca, Massimiliano; Caravelli, Silvio; Zaffagnini, Stefano (The Journal of Knee Surgery, 2020)
Long-term results of unicompartmental knee arthroplasty (UKA) have shown a slightly higher revision rate than total knee arthroplasty (TKA), and implant fixation geometry seems to affect prosthetic survivorship. Whether metal-backed tibial component leads to superior performance over the all-polyethylene design is unclear, and a lack of evidence exists in literature. Our purpose was to demonstrate which implant design of UKA (all-polyethylene or metal-backed tibial component) is clinically superior regarding revision rates and clinical functioning, and investigate the role of potential factors that could affect the revision rate. A systematic review was conducted for clinical studies comparing all-polyethylene and metal-backed tibial components used in primary UKAs in terms of revision rates and clinical scores. Meta-regression techniques were used to explore factors modifying the observed effect. All causes of revision were extracted and analyzed, to find statistically significant differences between the two groups. Our research strategy generated a systematic review of nine studies comprising 1,101 UKAs in 1,088 patients with 87 revisions for any reason. Meta-analysis showed a higher, but not statistically significant, risk of aseptic revision in the all-polyethylene group. Studies with a smaller sample size and higher percentage of female patients were correlated to a higher relative risk of revision in favor of all-polyethylene UKAs. Differently, patients' age and duration of follow-up did not influence the risk ratio. The main cause for revision was aseptic loosening in both implants' component, with no statistically differences in the two groups examined. Our results do not show a superiority of the metal-backed tibial component in UKAs in terms of survivorship, although extreme care must be given for patients with high risk of early failure, such as female patients. However, surgical experience, in combination with careful patient selection, remains paramount and may lead to better long-term outcomes in patients requiring UKA. This is a Level III, therapeutic study.
Keywords: unicompartmental knee arthroplasty; all-polyethylene; metal-backed; revision rate; aseptic loosening